Modulating residual stress based on atomic layer deposition to enhance the adhesion of parylene C for encapsulation of flexible organic light-emitting diodes. (1st April 2023) - Shangguan, Lianchao; Wang, Zhenyu; Chen, Ziqiang; Fan, Siyu; Li, Chuannan; Zhang, Jian; Wang, Muwei; Duan, Yu
Abstract: This paper proposes a method for enhancing the adhesion strength between parylene C and the substrate by depositing a layer of Al2 O3 film with residual tensile stress on parylene C by atomic layer deposition. Compared with pretreatment using a coupling agent, it improves the adhesion strength by 2.4 times. The parylene C/Al2 O3 hybrid film maintains a good barrier performance after 10 000 times of bending with a bending radius of 3 mm, with the water vapor transmission rate (WVTR) retained at 3.55 × 10 −4 g·m −2 ·d −1 . Encapsulation of flexible organic light-emitting diodes is carried out using this hybrid film without a negative effect on the performance.